Ahdaf Soueif's Cairo: a Mezzaterra found. Issue 6 (3rd June 2022) - Al Sahib, May
ABSTRACT: Ahdaf Soueif, who belongs to the generation known as Jil el-thawra (the generation of the revolution) of 1952, also lived to witness the January revolution of 2011. In Mezzaterra : Fragments from the Common Ground (2004) and Cairo : My City, Our Revolution (2012) Soueif narrates her quest for a cosmopolitan common ground. Even though cosmopolitanism is one of the main subject matters in both texts, they exhibit different types of cosmopolitanism, as the event of the revolution is in fact the utopian cosmopolitanism that she always hoped for. If in Mezzaterra this takes the form of a yearning for a utopian cosmopolitanism, it is in Cairo 's Tahrir that she finds this through its collective outlook.